Wet brewers’ grains as a source of protein for feedlot lambs: Impacts on intake, apparent nutrient digestibility, ruminal fermentation, and nitrogen balance - de Assis, Rhaíssa G.; dos Santos, Isabela J.; Gasparina, Jennifer M.; Bandoria, Natalia A.; Alves, Brenda; Dias, Paulo C.G.; Vicente, Ana C.S.; Soares, Letícia C.B.; Polizel, Daniel M.; Biava, Janaina S. [UNESP]; Pires, Alexandre V.; Ferreira, Evandro M. (Elsevier, 2023)
The aim of this study was to evaluate the effect of wet brewers’ grain (WBG) as an alternative ingredient replacing soybean meal (SBM) and ground corn (GC) on nutrient intake and apparent digestibility, ruminal fermentation characteristics, and nitrogen balance in feedlot lambs. Five ruminally cannulated ½ Dorper × ½ Santa Inês lambs, castrated with 48.3 ± 2.0 kg of initial BW and 8.3 ± 0.68-month-old (mean ± SD), were assigned in a 5 × 5 Latin square design. The experimental diets were composed of 10% roughage (Coastcross hay) and 90% concentrates, in which 85.9% of the diet was composed of GC (71.3%) plus SBM (14.6%) in the control diet. Treatments consisted in WBG inclusion levels of 7.6%, 15%, 23% and 30% replacing GC+SBM in control diet with the aim to maintain isonitrogenous concentrations. The data were analyzed using a linear or quadratic polynomial contrast in SAS. There was no effect of WBG inclusion on DMI, OM nor CP intake, but a linear increase was observed for NDF (P < 0.001), ADF (P < 0.001), EE intake (P < 0.01), and linear decrease (P < 0.001) on NFC intake. Inclusion of WBG decrease linearly NFC, while DM, OM, and CP digestibility were being lower for lambs fed a diet contained 23% WBG (quadratic component, p < 0.05). The replacement of SBM and corn grain by WBG, linearly increased the molar ratio of acetate (P < 0.01), and linearly decreased propionate (P < 0.01), resulting in a linear increase in the acetate:propionate ratio (P = 0.04). In addition, increasing the inclusion of WBG linearly increased the molar proportion of isovalerate (P < 0.05). Ruminal pH increased linearly (P < 0.001) by dietary WBG inclusion, as consequence, ruminal pH was maintained less time below 5.5 as WBG inclusion increased. Although nitrogen excretion was greater with 23% inclusion of WBG in diet (quadratic component, P < 0.05), there was no effect (P > 0.10) on retained N. Based on diet acceptability, digestibility, N retention, and ruminal fermentation parameters, it is concluded that, WBG can be used as feed ingredient up to 7.6% in diets, replacing partially SBM and GC in finishing diets for lambs. Inclusion WBG replacing SBM and partially GC, minimize the risk of acidosis in lambs fed high-concentrate diets during fattening. Inclusions beyond 23% decreased significant diet digestibility and increased ruminal acetate: propionate molar ratio, decreasing energy efficiency, increasing methane losses.
Keywords: Acetate; Co-product; NDF; Propionate; Protein; Ruminal pH